Production and Characterization of Chitosan from Shrimp (Penaeus semisulcatus ) Shell Waste of UAE: Production of Chitosan from Shrimp Shell Waste (Biological Sciences - PJSIR, 2010)
Chitosan was prepared from shrimp (Penaeus semisulcatus) shell waste by a chemical process involving demineralization, deproteinization and deacetylation; conversion of chitin to chitosan (deacetylation) was achieved by treatment with concentrated sodium hydroxide solution (55%) at room temperature (25 ºC). The present study was undertaken to evaluate the influence of deacetylation process during chitosan production on the physicochemical and functional properties of shrimp shell chitosan. Four experimental chitosan samples were prepared with deacetylation for 40 h, for 50 h, with and without stirring as well as for 60 h and were subjected to physicochemical and functional characteristic analysis. Change in duration of deacetylation process yielded some differences in each characteristic; deacetylation for 40 h led to lower viscosity, solubility, water/fat binding capacity and degree of deacetylation and for 60 h resulted in increase in solubility but decrease in viscosity. Stirring during deacetylation process led to lower viscosity, higher degree of deacetylation and higher fat binding capacity of the product. In contrast non-stirred sample produced product with lower degree of deacetylation and higher viscosity. It was concluded that duration of deacetylaylation process should be monitored constantly for optimal chitosan production depending on its intended usages in food, pharmaceutical and biomedical industries.